Linking Peer Relational Aggression Victimization to Internalizing Symptoms during Adolescence: A Narrative Review of Mediating and Moderating Mechanisms (European Journal of Behavioral Sciences, 2025)
Some studies indicated that relational aggression victimization may impact adolescents’ internalizing symptoms; however, no related research has been done to demonstrate theoretical perspectives and the mediating or moderating mechanisms of relational aggression victimization’s impact on internalizing symptoms during adolescence. Therefore, this paper conducted a narrative review and proposed a framework to understanding the mediating and moderating mechanisms of the relationship between relational aggression victimization and internalizing symptoms during adolescence. In conclusion, three mediating mechanisms have been found: (1) Negative Self-evaluation System, (2) Adverse Interpersonal Situation, and (3) Poor Quality of Friendships, and may be moderated by gender, emotional support, and rumination. Due to some questions and issues in this research field had not been answered well, we suggested some implications for future research in the end of the paper.